Ship to Shore: - Jeans, Peter D. (International Marine, 2004)
Bail out. The coast is clear. In deep water. These are just a few of the seafaring terms that have become part of our common language. But where do they come from, and what do they really mean? Peter Jeans provides all the answers in this book which was named a "Best Reference Source" by Library Journal. In his journey to uncover word origins, Jeans paints a vivid picture of hardy Nantucket whalers and Elizabethan sea dogs, grizzled Nova Scotia fishermen and the crews of great clipper ships. Along the way, he recounts the exploits of such seafaring greats as Sir Francis Drake, Captain Cook, and John Paul Jones. More than a dictionary, Ship to Shore is a fascinating chronicle of the sailing men who made an enduring contribution to the English language. Here readers will find origins of words and phrases such as: Listless, Peepers , To turn turtle , Sundowner, unstayed, To come in with flying colors, Blowhard, To be taken aback